2022
DOI: 10.3389/fonc.2022.865779
|View full text |Cite
|
Sign up to set email alerts
|

Low MxA Expression Predicts Better Immunotherapeutic Outcomes in Glioblastoma Patients Receiving Heat Shock Protein Peptide Complex 96 Vaccination

Abstract: Heat shock protein peptide complex 96 (HSPPC-96) has been proven to be a safe and preliminarily effective therapeutic vaccine in treating newly diagnosed glioblastoma multiforme (GBM) (NCT02122822). However, the clinical outcomes were highly variable, rendering the discovery of outcome-predictive biomarkers essential for this immunotherapy. We utilized multidimensional immunofluorescence staining to detect CD4+ CD8+ and PD-1+ immune cell infiltration levels, MxA and gp96 protein expression in pre-vaccination G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…HSP peptide complex-96 (HSPPC-96) is the most widely used to treat gliomas [ 787 ]. A trial in rGB patients tested this hypothesis and showed an increase in the mOS, a specific peripheral immune response to the peptides bound to HSPPC-96, a focal cellular infiltrate of CD4+ and CD8+ and, in addition, brain biopsies were consistent with specific immune responses at the tumor site [ 678 , 679 ]. A following phase II trial (NCT01814813) failed to demonstrate a survival benefit for patients treated with HSPPC-96 alone or in combination with BEV compared to BEV alone [ 680 ].…”
Section: Immunotherapiesmentioning
confidence: 99%
“…HSP peptide complex-96 (HSPPC-96) is the most widely used to treat gliomas [ 787 ]. A trial in rGB patients tested this hypothesis and showed an increase in the mOS, a specific peripheral immune response to the peptides bound to HSPPC-96, a focal cellular infiltrate of CD4+ and CD8+ and, in addition, brain biopsies were consistent with specific immune responses at the tumor site [ 678 , 679 ]. A following phase II trial (NCT01814813) failed to demonstrate a survival benefit for patients treated with HSPPC-96 alone or in combination with BEV compared to BEV alone [ 680 ].…”
Section: Immunotherapiesmentioning
confidence: 99%
“…Although patients with early-stage disease benefited significantly, the intent-to-treat population as a whole did not. The approach continues to be pursued today with better tools of immunization and monitoring ( 101 103 ). In the high-throughput DNA-sequencing era (2012 and onward), patients with melanoma ( 104 106 ), glioblastoma ( 107 , 108 ), pancreatic cancer ( 109 ), lung cancer ( 110 ), or bladder cancer ( 106 ) have been immunized with long peptides (or RNA encoding such peptides) containing neoepitopes that were predicted to be presented by MHC I.…”
Section: The Complexity: Mechanistic Expectations Versus Realitymentioning
confidence: 99%